2020
DOI: 10.1371/journal.pone.0230626
|View full text |Cite
|
Sign up to set email alerts
|

On the etiology of internalizing and externalizing problem behavior: A twin-family study

Abstract: Internalizing and externalizing behavior problems are established risk factors for many unpleasant outcomes and psychopathology in adulthood, and understanding the interplay between genes and environment is important for deducing implications for therapeutic interventions. Among genetic studies on internalizing and externalizing problem behavior, the heritability estimates differ widely. Most research only uses twin data and other-reports, and therefore certain limitations are inevitable. Our study is the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…We initially found that genome‐wide influences explained more than twice the variance in externalizing symptoms (19%) compared to internalizing symptoms (6%) at this age. This aligns with twin‐based literature, indicating externalizing symptoms are more heritable than internalizing symptoms in early adolescence (Bergen, Gardner, & Kendler, 2007 ; Nikstat & Riemann, 2020 ) – potentially due to measurement, as externalizing behaviors are more easily observed and potentially captured with reduced noise (Bartels et al., 2004 ), or life course timing, since depression and other internalizing conditions may onset later in adolescence and young adulthood (Nivard et al., 2017 ). Unlike twin studies that extrapolate genetic and environmental influences based on inherited similarities/differences, we examined common genomic variation in unrelated individuals.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We initially found that genome‐wide influences explained more than twice the variance in externalizing symptoms (19%) compared to internalizing symptoms (6%) at this age. This aligns with twin‐based literature, indicating externalizing symptoms are more heritable than internalizing symptoms in early adolescence (Bergen, Gardner, & Kendler, 2007 ; Nikstat & Riemann, 2020 ) – potentially due to measurement, as externalizing behaviors are more easily observed and potentially captured with reduced noise (Bartels et al., 2004 ), or life course timing, since depression and other internalizing conditions may onset later in adolescence and young adulthood (Nivard et al., 2017 ). Unlike twin studies that extrapolate genetic and environmental influences based on inherited similarities/differences, we examined common genomic variation in unrelated individuals.…”
Section: Discussionsupporting
confidence: 89%
“…Broadly speaking, it is known that both genetic and environmental factors play a role in influencing mental health among youth (Kwong et al., 2019 ; Nikstat & Riemann, 2020 ). However, a complete picture remains obscured by the limited focus of prior studies.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas demographic, perinatal, child dispositional, and family and broader social environmental predictors of joint internalizing/externalizing developmental trajectories have been studied, the role of genetic predisposition to mental health problems has only been indirectly considered through parental history of psychiatric illness. Yet, the heritability for both internalizing and externalizing difficulties is estimated to be above 30% (Nikstat & Riemann, 2020) and for externalizing difficulties as high as 80% (Hicks, Krueger, Iacono, McGue, & Patrick, 2004). The genetic architecture of internalizing and externalizing difficulties is complex with hundreds to thousands of genes contributing to their heritability and individual risk alleles typically only having very small effects.…”
Section: Introductionmentioning
confidence: 99%
“…Parent rating assimilation and contrast biases for various child behaviors have been demonstrated for monozygotic (MZ) and dizygotic (DZ) pairs, respectively (Bartels et al 2004;Saudino 2003). Self-reports also are prone to social report biases (Nikstat and Riemann 2020), as in all research. Court records may reflect social or cultural biases (Ahonen et al 2017;Stevens and Morash 2015).…”
mentioning
confidence: 94%